The combination of mineral fertilizer with organic fertilizer improved soil phosphorus availability - Yuxin Luo; Jing Liang; Chunliang Zhou (All Life)
Large amounts of use of mineral fertilizers (MF) have brought about environmental pollution and soil problems, like soil degradation and acidification. The partial substitution of MF with organic fertilizer is considered eco-friendly and more efficient in improving soil fertility. In our study, the effects of MF alone and the combination of MF and organic fertilizers (MOF) on soil phosphorus (P) availability in infertile soil with P deficiency were studied with the initial soil without any addition as the control. The addition of MF and MOF increased the soil labile P (resin-P and NaHCO3-Pi) by 101.8% and 320.1%, respectively, compared to the control after 180 days of treatment. Resin-P was the predominant P fraction in MOF, accounting for 28.0% of the total P. The proportions of residual-P in MOF were 5.6% and 8.3% lower than those in MF and control, respectively. The P activation coefficient in MOF was the highest (15.0%), and was the main contributor to soil P fractions based on redundancy analysis. Our results suggest that the combined application of organic and mineral fertilizers is more efficient in improving soil P availability than mineral fertilizer alone. We highlight the joint application was beneficial to improve soil P activation coefficient.